Evaluation of Concrete Strength with Scarified Road Waste Material - Mohammed, K.; Mustapha, Z. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The rising construction materials cost, dwindling materials availability and environmental challenges couple with the serious effect of construction waste have caused a serious concern in the construction industry. Most of the time, repairs of failed road pavements result in generation of Scarified Road Material Wastes (SRMW) and these are usually dumped by the roadsides thus causing environmental issues. These SRMWs could be useful if recycled in the production of concrete but their composition remains a question. Hence, this study seeks to investigate the suitability of SRMW in the production of concrete if used as fine aggregate. The fine aggregate content in nominal concrete mix was altered with SRMW that ranged between 0 – 40 % at an increment of 10%. Similarly, the SRMW was used as an additive in normal concrete mix. The casted concrete cubes of 150 x 150 x 150mm size were tested for strength on 7, 14, 21 and 28 days periods. The experimental results showed that the use of scarified road waste material in lieu of fine aggregates in concrete mixes yielded some promising characteristics. The study revealed that it can be useful in the production of light weight concrete within an optimum range of 10% replacement.